THE RELATION BETWEEN ISLAMIC EDUCATION ENVIRONMENT MANAGEMENT AND STUDENT EMOTIONAL INTELLIGENCE - Sari, Eliana (Jurnal Pendidikan Islam, 2016)
This study aims to find out the degree of the relationship between the implementation of Islamic education management of school environment and students’ emotional intelligence. The theory underlying in this study is the management of school environment (Ki Hajar Dewantara), and emotional intelligence (Shapiro and Goleman). This study used correlational study. Respondents were female students of Islamic educational institutions in Bekasi City, West Java, Indonesia. The result shows that the relation degree between the implementation of the management of Islamic education of school environment and students’ emotional intelligence is quite significant (0, 907%). This means that if the management of Islamic education of school environment enhances effectively, the implementation of one percent of students’ emotional intelligence will increase by 0, 907%. This study also finds that the management of Islamic education of school environment can be a preventive and anticipatory solution for students’ deviant behaviors.